Long-Term Outcomes Following Inguinal Hernia Repair With Mesh Performed by Medical Doctors and Surgeons in Ghana - Jessica H. Beard, MD; Michael Ohene-Yeboah, MBChB; Emmanuel S. Kasu, MBChB; Nelson Affram, MBChB; Stephen Tabiri, MD; Joachim K. A. Amoako, MBChB; Francis A. Abantanga, MD; Jenny Löfgren, MD (Annals of Surgery Open)
Objective:. To assess long-term outcomes following inguinal hernia repair with mesh performed by medical doctors and surgeons in Ghana. Background:. Task sharing of surgical care with nonsurgeons can increase access to essential surgery. Long-term safety and outcomes of task sharing are not well-described for hernia repair. Methods:. This prospective cohort study was conducted in Ho, Ghana. After completing a training course, 3 medical doctors and 2 surgeons performed inguinal hernia repairs with mesh on men with primary, reducible hernias. The primary outcome of this study was hernia recurrence at 5 years. The noninferiority limit was 5 percentage points. Secondary endpoints included pain and self-assessed health status at 5 years. Results:. A total of 242 operations in 241 participants were included, including 119 hernia repairs performed by the medical doctors and 123 performed by the surgeons. One hundred and sixty-nine participants (70.1%) were seen in follow-up at 5 years, 29 participants (12.0%) had died and 43 (17.8%) were lost to follow-up. The overall 5-year recurrence rate was 4.7% (n = 8). The absolute difference in recurrence rate between the medical doctor group (2 [2.3%]) and the surgeon group (6 [7.3%]) was −5.0 (1-tailed 95% confidence interval, −10.5; P = 0.06), demonstrating noninferiority of the medical doctors. Participants experienced improvements in groin pain and self-assessed health status that persisted at 5 years. Conclusions:. Long-term outcomes of elective mesh inguinal hernia repair in men performed by medical doctors and surgeons in Ghana were excellent. Task sharing is a critical tool to address the substantial morbidity of unmet hernia surgery needs in Ghana.